1988
DOI: 10.1002/bip.360270510
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction of chromomycin A3 with calf thymus DNA in the presence of metal cations at different pH values

Abstract: SynopsisThe interactions of the antitumor antibiotics, chromomycin A,, with a variety of metal cations in the pH range of 3.0-8.5 were systematically studied by CD, absorption, and 'H-nmr spectroscopies. Results were compared with thaw obtained in the presence of increasing amounts of calf thymus DNA. The negatively charged chromomycin A,, pK, 6.3, forms aggregates that become ordered and smaller in size, in the presence of variety of metal cations. Spectrophotometric titrations have shown that binding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Footprinting studies have also shown that both Chro and Mith require a G-C binding site that is at least three base pairs long (5,10). In addition to Mg 2+ , other divalent cations with a radius <0.85 A Ê are candidates for drug dimer formation (15,16). The solution structures of both complexes including the Mg 2+ -coordinated Chro±DNA complex (two drug equivalents per duplex) have been analyzed by nuclear magnetic resonance (NMR) spectroscopy (17±20).…”
Section: Introductionmentioning
confidence: 99%
“…Footprinting studies have also shown that both Chro and Mith require a G-C binding site that is at least three base pairs long (5,10). In addition to Mg 2+ , other divalent cations with a radius <0.85 A Ê are candidates for drug dimer formation (15,16). The solution structures of both complexes including the Mg 2+ -coordinated Chro±DNA complex (two drug equivalents per duplex) have been analyzed by nuclear magnetic resonance (NMR) spectroscopy (17±20).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, only a few reports have appeared on this topic using CD spectroscopy [15,19,221. However, this technique is very interesting because of the large CD signal exhibited by these molecules and because of the sensitivity of the CD signal to a small modification in the molecular conformation.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to now, conflicting values have been reported. Thus, Najak et al [I41 and Weinberger et al [15] have reported pK, values of 7 and 6.3, respectively. These determinations were performed at a drug concentration of approximately 50 pM and a varying temperature, most probably room temperature.…”
Section: Spectroscopic Studies Of Mit As a Function Of Its Protonatiomentioning
confidence: 99%
See 1 more Smart Citation
“…While it is frequently considered that the presence of Mg2+ constitutes an absolute requirement for binding to occur [ 11,121, with, however, differing views on the ion's exact role and positioning [3,4,10], a recent publication [13] indicates that at pH 4.5 binding of the drug, which is present then in neutral monomeric form, does not require divalent cations (although the strength of binding is greatly enhanced in their presence). At pH > 7.0 and low DNA/drug ratios (< 20), metal cations are necessary, but at high DNA/drug ratios an appreciable proportion of the drug is bound even in the absence of the metal.…”
Section: Introductionmentioning
confidence: 99%